Comportamiento de la resistencia a la compresión axial del microconcreto para modelos a escala reducida - Valverde-Vindas, Steven Francisco (Instituto Tecnológico de Costa Rica, 2018)
The following study shows the corresponding results of making microconcrete mixtures in cylinders on a reduced scale, using three different water-cement ratios (0,4; 0,5; 0,6), four percentages of aggregate (20%, 30%, 40% 50%) and cement type UG (general use). The purpose of the project was to determine the variation of the resistance of the microconcrete mixtures according to different dosages. At the end of the faults and obtaining the results of the axial compression resistances, a statistical analysis of all the values obtained was carried out, to evaluate if they followed a normal behavior. An analysis of variance (ANOVA) was also performed to determine which factors influenced the resistance. Added to this, a Tukey test is performed. Based on Tukey's test, it is affirmed that with an A/C ratio of 0,4 and 40% of aggregate, the mixture with the highest resistance performance at 28 days was obtained, which corresponds to an average value of 44,26 MPa and the lower strength was obtained from the mixture with an A/C ratio of 0,6 and 20% aggregate with a resistance of 14,76 MPa. Finally, resistance development curves are presented with age, where it is determined that the resistance acquired after 7 days is between 55% and 73% of the final resistance reached by the specimens.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Construcción, 2018.
Keywords: Concreto; Cemento; Agua; Resistencia; Mezcla